2020
DOI: 10.3390/app10217408
|View full text |Cite
|
Sign up to set email alerts
|

Lower Back Complaints in Adolescent Competitive Alpine Skiers: A Cross-Sectional Study

Abstract: Background: Little is known about lower back complaints in adolescent competitive alpine skiers. This study assessed their prevalence and severity (i.e., intensity and disability) with respect to sex, category, discipline preference, and training attributes. Methods: 188 competitive skiers aged 15 to 18 years volunteered in this study. Data collection included (i) questions on participants’ demographics, sports exposure, discipline preferences, and other sports-related practices; (ii) the Nordic Musculoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Adolescent athletes involved in sports that have repetitive extension, flexion, and rotation of the spine (e.g., gymnastics, soccer, dance) are the most susceptible to injuries in the lower back (17). Furthermore, a study on adolescent alpine skiers aged 15-18 years, that used a similar methodology as our study, reported that 80.3% of skiers suffered LBP during the last 12 months, and 50.7% during the last 7 days, which is a higher prevalence than in our study (38). Moreover, LBP among young alpine skiers was in 21.8% of cases classified as high intensity/low disability, which is of significantly higher prevalence than in our study (6%).…”
Section: The Prevalence Of Low Back Pain In Adolescent Climberssupporting
confidence: 52%
“…Adolescent athletes involved in sports that have repetitive extension, flexion, and rotation of the spine (e.g., gymnastics, soccer, dance) are the most susceptible to injuries in the lower back (17). Furthermore, a study on adolescent alpine skiers aged 15-18 years, that used a similar methodology as our study, reported that 80.3% of skiers suffered LBP during the last 12 months, and 50.7% during the last 7 days, which is a higher prevalence than in our study (38). Moreover, LBP among young alpine skiers was in 21.8% of cases classified as high intensity/low disability, which is of significantly higher prevalence than in our study (6%).…”
Section: The Prevalence Of Low Back Pain In Adolescent Climberssupporting
confidence: 52%
“…25 Furthermore, pain intensity was significantly associated with years of sport participation, number of competitions per season, and number of ski days per season in adolescent competitive alpine skiers. 2 Studies on adult elite skiers showed that overuse-related back complaints occur both in the preparation phase (off-and on-snow training) and during the competition season. 11,12 The role of the lumbar multifidus (LMF) in overuse-related back complaints has been studied extensively.…”
mentioning
confidence: 99%
“…Musculoskeletal complaints are common symptoms in general and athletic populations across the lifespan 1–3 . Among these, neck pain (NP) is considered one of the main causes of disability worldwide, with approximately 50% of the population will experience a clinically relevant NP episode throughout their lifetime 4 .…”
mentioning
confidence: 99%